Triangles Rotating

Geometry Level 4

Δ 1 { \Delta }_{ 1 } is an equilateral triangle with unit length and we have a function f ( x ) f(x) which is used to create other triangles.

We create further triangles with the following rules

We take Δ n { \Delta }_{ n } 's side and produce it's sides clockwise till it's new length is f ( n ) f(n) times the original length,and the final end points are joined to make Δ n + 1 { \Delta }_{ n+1 }

For example, if f ( x ) = 2 f(x)=2 Here if the B l u e \color{#3D99F6}{Blue} triangle is Δ n { \Delta }_{ n } then the R e d \color{#D61F06}{Red} triangle is Δ n + 1 { \Delta }_{ n+1 } ,and the ratio of lengths B l u e + O r a n g e B l u e \frac { \color{#3D99F6}{Blue}+ \color{#EC7300}{Orange} }{ \color{#3D99F6}{Blue} } = = f ( n ) f(n) ,and the triangle rotates by 0.3334 0.3334 radians

If f ( n ) = 2 3 n 2 1 2 3 n 2 3 f(n)=\frac { 2\sqrt { 3 } { n }^{ 2 }-1 }{ 2\sqrt { 3 } { n }^{ 2 }-3 } , find the total rotation of Δ n { \Delta }_{ n } in radians when compared to Δ 1 { \Delta }_{ 1 } as n n\rightarrow \infty .


The answer is 0.785398163397.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Let x n denote the side length of the triangle Δ n In the above figure, applying sine rule for the GREEN triangle,we get \begin{aligned} &\text{Let } x_{n} \text{ denote the side length of the triangle } \Delta_{n}\\ &\text{In the above figure, applying sine rule for the } \color{#20A900}\text{GREEN}\color{#333333}\text{ triangle,we get} \end{aligned}

( f ( n ) 1 ) x n sin θ n = f ( n ) x n sin ( 60 θ n ) = x n + 1 sin ( 12 0 ) f ( n ) f ( n ) 1 = sin ( 60 θ n ) sin θ n ( 1 ) We have, f ( n ) f ( n ) 1 = 1 1 1 f ( n ) = 1 1 2 3 n 2 3 2 3 n 2 1 f ( n ) = 2 3 n 2 1 2 3 n 2 3 (Given) = 2 3 n 2 1 2 ( 2 ) Also, sin ( 60 θ n ) sin θ n = sin ( 60 θ n ) sin ( 6 0 ) sin θ n sin ( 6 0 ) = sin ( 6 0 ) × ( cot θ n cot ( 6 0 ) ) sin ( A B ) sin A sin B = cot B cot A = 3 2 cot θ n 1 2 ( 3 ) From ( 1 ) , ( 2 ) and ( 3 ) , we get 3 2 cot θ n 1 2 = 2 3 n 2 1 2 cot θ n = 2 n 2 θ n = cot 1 ( 2 n 2 ) We are required to find the total angle which is given by, n = 1 θ n = n = 1 cot 1 ( 2 n 2 ) = n = 1 tan 1 ( 1 2 n 2 ) = n = 1 tan 1 ( 2 4 n 2 ) = n = 1 tan 1 ( 2 1 + ( 4 n 2 1 ) ) = n = 1 tan 1 ( ( 2 n + 1 ) ( 2 n 1 ) 1 + ( 2 n + 1 ) ( 2 n 1 ) ) = n = 1 tan 1 ( 2 n + 1 ) tan 1 ( 2 n 1 ) We can see that the above sum telescopes n = 1 θ n = tan 1 ( ) tan 1 ( 1 ) = π 2 π 4 = π 4 0.7853 \begin{aligned} \dfrac{(f(n)-1)x_{n}}{\sin\theta_{n}}&=\dfrac{f(n)\cdot x_{n}}{\sin(60-\theta_{n})}=\dfrac{x_{n+1}}{\sin(120^{\circ})}\\ \implies\dfrac{f(n)}{f(n)-1}&=\dfrac{\sin(60-\theta_{n})}{\sin\theta_{n}}\hspace{4mm}\color{#3D99F6}\small (1)\\\\ \text{We have,}\\ \dfrac{f(n)}{f(n)-1}&=\dfrac{1}{1-\dfrac{1}{f(n)}}\\ &=\dfrac{1}{1-\dfrac{2\sqrt3 n^2-3}{2\sqrt3 n^2-1}}\hspace{4mm}\color{#3D99F6}\small f(n)=\dfrac{2\sqrt3 n^2-1}{2\sqrt3 n^2-3}\hspace{2mm}\text{(Given)}\\ &=\dfrac{2\sqrt3 n^2-1}{2}\hspace{4mm}\color{#3D99F6}\small (2)\\\\ \text{Also,}\hspace{7mm}&\\ \dfrac{\sin(60-\theta_{n})}{\sin\theta_{n}}&=\dfrac{\sin(60-\theta_{n})\cdot \sin(60^{\circ})}{\sin\theta_{n} \cdot\sin(60^{\circ})}\\ &=\sin(60^{\circ})\times(\cot\theta_{n}-\cot(60^{\circ}))\hspace{6mm}\color{#3D99F6}\small\dfrac{\sin(A-B)}{\sin A \cdot\sin B}=\cot B-\cot A\\ &=\dfrac{\sqrt3}{2} \cot\theta_{n}-\dfrac12\hspace{4mm}\color{#3D99F6}\small (3)\\\\ \text{From } \color{#3D99F6}(1), (2) \color{#333333}& \text{ and }\color{#3D99F6} (3), \color{#333333}\text{ we get}\\ \dfrac{\sqrt3}{2} \cot\theta_{n}-\dfrac12&=\dfrac{2\sqrt3 n^2-1}{2}\\ \cot\theta_{n}&=2n^2\\ \theta_{n}&=\cot^{-1} (2n^2)\\\\ \text{We are required to } &\text{find the total angle which is given by,}\\ \sum_{n=1}^{\infty}\theta_{n}&=\sum_{n=1}^{\infty}\cot^{-1} (2n^2)\\ &=\sum_{n=1}^{\infty}\tan^{-1} \left(\dfrac{1}{2n^2}\right)\\ &=\sum_{n=1}^{\infty}\tan^{-1} \left(\dfrac{2}{4n^2}\right)\\ &=\sum_{n=1}^{\infty}\tan^{-1} \left(\dfrac{2}{1+(4n^2-1)}\right)\\ &=\sum_{n=1}^{\infty}\tan^{-1} \left(\dfrac{(2n+1)-(2n-1)}{1+(2n+1)\cdot (2n-1)}\right)\\ &=\sum_{n=1}^{\infty}\tan^{-1}(2n+1)-\tan^{-1}(2n-1)\\ \text{We can see that}&\text{ the above sum telescopes}\\ \implies\sum_{n=1}^{\infty}\theta_{n}&=\tan^{-1}(\infty)-\tan^{-1}(1)\\ &=\dfrac{\pi}{2}-\dfrac{\pi}{4}\\ &=\dfrac{\pi}{4}\approx\color{#EC7300}\boxed{\color{#333333}0.7853}\end{aligned}

The third angle is 60-theta instead of 120-theta.

A Former Brilliant Member - 2 years, 2 months ago

Thanks for noticing ,i will fix it!

Anirudh Sreekumar - 2 years, 2 months ago

Could someone point out my mistake i can't seem to fix this

Anirudh Sreekumar - 2 years, 2 months ago

Log in to reply

It might be i made the same mistake as you,i will edit this f(n) shortly

Shauryam Akhoury - 2 years, 2 months ago

Does f ( n ) = 2 3 n 2 1 2 3 n 2 3 f(n)=\frac { 2\sqrt { 3 } { n }^{ 2 }-1 }{ 2\sqrt { 3 } { n }^{ 2 }-3 } work?

Shauryam Akhoury - 2 years, 2 months ago

Log in to reply

yp, i think so

Anirudh Sreekumar - 2 years, 2 months ago

Log in to reply

@Anirudh Sreekumar Thanks, i edited it,but funny thing,i got correct angels for 3 different f(n)'s even with my wrong result

Shauryam Akhoury - 2 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...